2017
DOI: 10.16965/ijar.2017.127
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Anthropometric Study of Height and Sex Determination Using Percutaneous Ulnar and Femoral Lengths

Abstract: Osteometric indices have a direct relationship with sex, height, age and race of an individual. These factors play a pivotal role in the identification of an individual. There are very few reports in Ghana on the use of bones for personal identification as compared to the developed world. Therefore the present study sought to use the ulna and femur as models for height and sex determination. One hundred undergraduate students of the Kwame Nkrumah University of Science and Technology, Kumasi made up of 55% male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…Its reliability was evaluated in the test group with 95 -100% accuracy. Based on the literature, forearm length is a reliable measure for sex determination in other populations based on surface anthropometric and osteological landmarks (8,18). According to Ahmed on Sudanese adults, forearm length with surface anthropometric landmarks was the most reliable parameter for sex determination with 78.5 and 89.5% accuracy among the four main upper limb dimensions, similar to our study (14).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Its reliability was evaluated in the test group with 95 -100% accuracy. Based on the literature, forearm length is a reliable measure for sex determination in other populations based on surface anthropometric and osteological landmarks (8,18). According to Ahmed on Sudanese adults, forearm length with surface anthropometric landmarks was the most reliable parameter for sex determination with 78.5 and 89.5% accuracy among the four main upper limb dimensions, similar to our study (14).…”
Section: Discussionsupporting
confidence: 85%
“…The mean statures were significantly higher for males than for females in the present study. The shorter length in females is created due to high estrogen levels during pu- berty, which leads to earlier stopping of bone growth (18). Unlike females, because of high testosterone levels, males have more bone growth opportunities that eventually lead to longer bones (18).…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal influences during puberty causes earlier cessation of bony growth in females than the males, as it has underlying effects on the pattern and duration of growth. The females undergo accelerated pubertal growth spurt, ending their growth faster than the males who experience more sustained growth (Ansah et al 2017). Frey (2000) also reported that women generally tend to have a narrower heel in relation to the forefoot and narrow feet than men relative to length.…”
Section: Sexual Dimorphism In Stature and Foot Dimensionsmentioning
confidence: 99%
“…Among these measurements, the stature estimation from long bones becomes imperative, while the direct height measurement is difficult, especially in debilitated, bedridden persons or in persons that may have vertebral column or limbrelated problems [21]. The measurement from long bones includes the upper arm length [22] or humeral length [23,24], tibial length [23,25], femoral length [26], fibula length [25,27], radial length [28][29][30][31] and ulnar length [26][27][28][29][30][31][32][33][34][35] etc. Further, it has also been found that the lower extremities are strongly correlated with stature than upper extremities [36].…”
Section: Introductionmentioning
confidence: 99%